2014
DOI: 10.1007/s00251-014-0790-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of CTLs regulated by rapamycin using RNA-Seq

Abstract: Memory programming of CTLs by inflammatory cytokines can be regulated by mTOR. We have shown that inhibition of mTOR during CTL activation leads to the enhancement of memory, but the molecular mechanisms remain largely unknown. Using high-throughput RNA-Seq, we identified genes and functions in mouse CTLs affected by mTOR inhibition through rapamycin. Of the 43,221 identified transcripts, 184 transcripts were differentially expressed after rapamycin treatment, corresponding to 128 annotated genes. Of these gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
(81 reference statements)
0
7
1
Order By: Relevance
“…Memory formation is the gold standard for vaccination, IL-12 is required for memory CTL formation, and IL-12 signaling can be regulated by other regulators, such as rapamycin 30 , 44 , 45 . To test the involvement of exosomes in this IL-12-driven memory programing, GW4869, an nSMase2 inhibitor 27 , 46 50 used largely in vitro rather than in vivo 51 , was added in the presence of IL-12 stimulation for naïve CD8 + T cells 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Memory formation is the gold standard for vaccination, IL-12 is required for memory CTL formation, and IL-12 signaling can be regulated by other regulators, such as rapamycin 30 , 44 , 45 . To test the involvement of exosomes in this IL-12-driven memory programing, GW4869, an nSMase2 inhibitor 27 , 46 50 used largely in vitro rather than in vivo 51 , was added in the presence of IL-12 stimulation for naïve CD8 + T cells 22 .…”
Section: Resultsmentioning
confidence: 99%
“…In CD8 + T-cells, mTORC1 controls, for example, glucose uptake and glycolysis during activation and effector phases and also participates in the signaling generated by the antigen recognition receptor (TCR) and cytokines ( Jacobs et al., 2008 ; Buck et al., 2015 ; Chang and Pearce, 2016 ). Even though rapamycin has been commonly used in organ transplantation to prevent graft rejection ( Augustine et al., 2007 ), several studies have reported that mTOR inhibition by treatment with low and continuous doses of rapamycin during the immune challenge of CD8 + T cells could improve the function and memory formation following viral infections or tumor challenges ( Araki et al., 2009 ; Rao et al., 2010 ; Li et al., 2011 ; Turner et al., 2011 ; Bassett et al., 2012 ; Mattson et al., 2014 ; Shrestha et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptome of activated CD8 + T cells treated with rapamycin revealed that most genes modulated by mTOR inhibitor are associated with apoptosis, survival, maintenance, and cell migration, which take part in the CD8 + T cell programming after activation ( Mattson et al., 2014 ; Borsa et al., 2019 ). Moreover, a clinical trial found that elderly people immunized against influenza and treated with rapamycin had a response 20% higher in antibody titer than the placebo group, paralleled by increased T cells life span, improving immune function and reducing infections ( Mannick et al., 2014 ; Mannick et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using 1.5-fold as the cutoff, 467 proteins were enhanced (or unique) in D1E (Supplementary Table 2), and 233 in D3E (Supplementary Table 3). We next explored how these skewed (differential) protein profiles were associated with downstream effector function using Ingenuity Pathway Analysis (IPA) (73). The two different profiles were predicted to relate to similar biological functions, such as enhancing the activation, movement of cells, inhibiting apoptosis, and cell death (Table 1).…”
Section: Resultsmentioning
confidence: 99%